2022
DOI: 10.1111/myc.13424
|View full text |Cite
|
Sign up to set email alerts
|

Acitretin: Could it be a new therapeutic player in the field of onychomycosis?

Abstract: Onychomycosis is a chronic fungal infection of the nail, characterised by nail discoloration, subungual hyperkeratosis and onycholysis.The involved pathogens are dermatophytes, yeasts (Candida spp.) and non-dermatophyte moulds (NDMs). 1 Dermatophytes such as Trichophyton rubrum and Trichophyton mentagrophytes are the most common agents of onychomycosis, with higher prevalence of the infection in toenails than in fingernails. Candida albicans affects almost exclusively the fingernails and accounts for 10% of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…By preventing hyphal germination necessary for biofilm formation, all-trans retinoic acid may also be effective against Candida biofilm-related infections, which are typically difficult to treat due to multidrug resistance [ 97 ]. In a study performed after our systematic search on 135 patients with toenail and/or fingernail onychomycosis receiving oral itraconazole pulse monotherapy, oral acitretin monotherapy, or combined pulsed itraconazole and acitretin for 3 months [ 98 ], mycological cure was 51.1%, 28.9%, and 80%, respectively, and complete cure was 20%, 28.9%, and 53.3%, respectively ( p ≤ 0.05). OSI scores significantly improved in the combination group compared to itraconazole monotherapy ( p = 0.005) and acitretin monotherapy ( p = 0.006) groups, with no difference observed between the monotherapy groups ( p = 0.95).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…By preventing hyphal germination necessary for biofilm formation, all-trans retinoic acid may also be effective against Candida biofilm-related infections, which are typically difficult to treat due to multidrug resistance [ 97 ]. In a study performed after our systematic search on 135 patients with toenail and/or fingernail onychomycosis receiving oral itraconazole pulse monotherapy, oral acitretin monotherapy, or combined pulsed itraconazole and acitretin for 3 months [ 98 ], mycological cure was 51.1%, 28.9%, and 80%, respectively, and complete cure was 20%, 28.9%, and 53.3%, respectively ( p ≤ 0.05). OSI scores significantly improved in the combination group compared to itraconazole monotherapy ( p = 0.005) and acitretin monotherapy ( p = 0.006) groups, with no difference observed between the monotherapy groups ( p = 0.95).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Retinoids have immunomodulatory and fungistatic activity against dermatophytes and Candida albicans [42] and increase nail growth rate via increased epidermal turnover [35]. It has been hypothesized that systemic retinoids may serve a therapeutic adjuvant role in the treatment of onychomycosis [35].…”
Section: Introductionmentioning
confidence: 99%
“…Mycological and complete cures were achieved in 51.1 and 20% of the itraconazole group, 28.9 and 28.9% of the acitretin group, and 80.0 and 53.3% in the combined itraconazole/acitretin group (mycological cure p ≤ 0.05 and clinical cure p = 0.007), respectively. Cheilitis was reported in 44.4% (20/45) of the oral acitretin group and 57.7% (26/45) of the combined itraconazole/acitretin therapy group [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14] Additionally, Campione et al 15 reported the successful use of topical 0.1% tazarotene gel in the treatment of onychomycosis. Furthermore, Nasr et al 16 have recently demonstrated favourable clinical and mycological outcomes of acitretin (25 mg/day for 3 months) in onychomycosis, with significantly superior efficacy when combined with oral itraconazole pulse therapy. Similarly, isotretinoin has been found to be a good adjuvant treatment for recalcitrant dermatophytosis due to its keratolytic and immunomodulatory effects.…”
Section: Introductionmentioning
confidence: 99%